The Antibacterial Activity of Pangi Kernel Extract (Pangium edule Reinw) towards Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa and Escherichia coli in Vitro - Makagansa, Christine; Mamuaja, Christine F.; Mandey, Lucia C. (Jurnal Ilmu dan Teknologi Pangan, 2015)
The aim of this research was to determine the phytochemical content of aquadest extract from pangi kernel (Pangium edule Reinw),and study the antibacterial activity on bacterial growth inhibition of Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa andEscherichia coli. Extraction was carried out done by maceration using aquadest. Analysis of phytochemicals were based on total phenolic and condensed tannins contents. Total phenolic content were 113.367 mg/kg and condensed tannins were 26,744 mg/kg for in 10.000 ppm extract.Â  Antibacterial activity test was carried out done by using paper disk diffusion method. Extract concentrations of 4%, 6% and, 8% were effectively inhibited Staphylococcus aureus growth,while extract concentration of 2%, 4%, 6% and 8% were efectively inhibited Bacillus cereus respectively. For Escherichia coli and Pseudomonas aeruginosa concentration extract of 2% did not show bacterial inhibition activity, but in concentration extract of 4%, 6% and 8% showed an effective inhibition activity. Keywords : antibacterial activity, Bacillus cereus, Escherichia coli, Pangium edule Reinw,Â  Pseudomonas aeruginosa, Staphylococcus aureus